Coronary heart disease clinical manifestation and risk factors in Japanese immigrants and their descendents in the city of São Paulo - Amato,Reynaldo Vicente (2003)
OBJECTIVE: To assess whether a difference exists in coronary heart disease clinical manifestations and the prevalence of risk factors between Japanese immigrants and their descendents in the city of São Paulo. METHODS: Retrospective analysis of coronary artery disease clinical manifestations and the prevalence of risk factors, comparing 128 Japanese immigrants (Japanese group) with 304 Japanese descendents (Nisei group). RESULTS: The initial manifestation of the disease was earlier in the Nisei group (mean = 53 years), a difference of 12 years when compared with that in the Japanese group (mean = 65 years) (P<0.001). Myocardial infarction was the first manifestation in both groups (P = 0.83). The following parameters were independently associated with early coronary events: smoking (OR = 2.25; 95% CI = 1.35-3.77; P<0.002); Nisei group (OR = 10.22; 95% CI = 5.64-18.5; P<0.001); and female sex (OR = 5.04; 95% CI = 2.66-9.52; P<0.001). CONCLUSION: The clinical presentation of coronary heart disease in the Japanese and their descendents in the city of São Paulo was similar, but coronary heart disease onset occurred approximately 12 years earlier in the Nisei group than in the Japanese group.